Rubik’s Cube Encryption Algorithm-Based Technique for Information Hiding During Data Transmission in Sensor-Based Networks - Balkrishna Salunke, Mahendra; Narendra Mahalle, Parikshit; Rahul Shinde, Gitanjali (International Journal of Intelligent Systems and Applications in Engineering, 2022)
The rise of the Internet of Things has created new opportunities for individuals and businesses in various industries such as healthcare, transportation, and manufacturing. However, it is important that the security of the data collected by these devices is taken seriously. To ensure that the data is secure, various types of cryptographic primitives have been used in various security solutions. These primitives are generally not designed to preserve the privacy or support advanced functionalities. Here we used Rubik’s cube encryption principle for secure data transmission. The original image is then scrambled using the algorithm of the famous cube, which is known as the XOR operator. Two secret keys are then used to encrypt the rows and columns of the image. The proposed system can be used to achieve strong encryption and flawless concealment, but can also withstand exhaustive, statistical, and differential attacks. Information security is currently the most significant concern. Whether the data is image or word, it must be protected. This study proposes a method for the secure transmission of data. The paper proposes a method that involves scrambling a three-dimensional color image matrix using a combination of operations.